Environmental Impacts of Microplastics and Nanoplastics: A Current Overview - Amobonye, Ayodeji; Bhagwat, Prashant; Raveendran, Sindhu; Singh, Suren; Pillai, Santhosh (Frontiers in Microbiology, 2021)
The increasing distribution of miniaturised plastic particles, viz., microplastics (100 nm - 5 mm) and nanoplastics (less than 100 nm), across the various ecosystems is currently a subject of major environmental concern. Exacerbating these concerns is the fact that microplastics and nanoplastics display different properties from their corresponding bulk materials, thus, not much is understood about their full biological and ecological implications. Currently, there are evidence to prove that these miniaturised plastic particles release toxic plastic additives and can adsorb various chemicals, thereby serving as sinks for various poisonous compounds, enhancing their bioavailability, toxicity and transportation. Furthermore, there is a potential danger for the trophic transfer of microplastics and nanoplastics to humans and other higher animals, after being ingested by lower organisms. Thus, this paper critically analyses our current knowledge with regard to the environmental impacts of microplastics and nanoplastics. In this regard, the properties, sources, and damaging effects of microplastics and nanoplastics on different habitats, particularly on the biotic components, were elucidated. Similarly, the consequent detrimental effects of these particles on humans as well as the current and future efforts at mitigating these detrimental effects, were discussed. Finally, the self-cleaning efforts of the planet via a range of saprophytic organisms on these synthetic particles were also highlighted.